2(2x + 1) = x + 15 + 2x
4x + 2 = 3x + 15
4x + 2 - 3x = 3x + 15 - 3x
x + 2 = 15
x + 2 - 2 = 15 - 2
x = 13
- - - - - - - - -s-
2007-03-31 11:09:08
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
The idea will be to isolate all the x terms on one side of the equation and everything else on the other. First multiply the left side out: 2(2x + 1) = 4x + 2. Combine the x terms on the right side, x + 2x = 3x. Now consolidate: 4x + 2 = 3x + 15. Then subtract 3x from both sides, and simplify again: 4x - 3x + 2 = 3x - 3x + 15; now subtract 2 from both sides and simplify again: x + 2 - 2 = 15 - 2 = 13 => x = 13. All such problems are solved by this method. Isolate the variable and then begin consolidating and simplifying until you can't any more. Your answer will pop out t that moment if not sooner.
2007-03-31 18:53:54
·
answer #2
·
answered by flyfisher_20750 3
·
0⤊
0⤋
2(2x+1)=x+15+2x
4x+2=x+15+2x multiple out the left side
4x+2=3X+15 add the x's on the right side
4x+2-2=3x+15-2 subtract 2 from both sides
4x=3x+13
4x-3x=3x+13-3x move all the x's to the left side by subtracting 3 x from both sides
1X=13 divide both sides my 1
x=13
2007-03-31 18:12:04
·
answer #3
·
answered by Kevin K 2
·
0⤊
0⤋
2(2x+1)=x+15+2x
distributive property
4x+2=x+15+2x
add like terms
4x+2=3x+15
minus three x on both sides
x+2=15
minus 2 on both sides
x=13
2007-03-31 18:12:49
·
answer #4
·
answered by :) 5
·
0⤊
0⤋
2(2x+1)=x+15+2x
2(2x+1)=3x+15 combined the terms with x
4x+2=3x+15 removed ()'s left side
4x+2 - 3x = 15 moved 3x across = and changed sign!
(easiest way to think)
4x-3x=15-2 moved 2 across = and again changed sign. Then x=13. Terms moved across = change sign. Factors ,however move up if down and down if up. Learn This!
2007-03-31 18:48:40
·
answer #5
·
answered by rwbblb46 4
·
0⤊
0⤋
4x + 2 = x + 15 + 2x
4x + 2 = 3x + 15
-3x, -2 -3x -2
x=13
2007-03-31 18:02:15
·
answer #6
·
answered by pazanski608 2
·
0⤊
0⤋
expand the brackets
collect like terms and simplify
So ...
2 (2x + 1) = x + 15 + 2x
therefore
4x + 2 = x + 15 + 2x {using distributive property on LHS}
3x + 2 = 15 + 2x {subtract x from both sides}
x + 2 = 15 {subtract 2x from both sides}
...
Ah well - as the answer has been provided for you now ...
x = 13 {subtract 2 from both sides}
2007-03-31 18:00:35
·
answer #7
·
answered by Orinoco 7
·
0⤊
0⤋
2 (2x + 1) = x + 15 + 2x
first, expand out all terms:
4x+2=x+15+2x
next, get all of your 'x' terms on one side and all other terms on the other:
4x-x-2x=15-2
simplify these terms:
x=13
2007-03-31 18:37:31
·
answer #8
·
answered by math_whiz 2
·
0⤊
0⤋
2(2X+1)=X+15+2X
4X+2=3X+15 (COMBINE LIKE TERMS)
X=13 (SUBTRACT 3X FROM BOTH SIDES, AND 2 FROM EACH SIDE) HOPE THIS HELPS
2007-03-31 18:04:04
·
answer #9
·
answered by tlfdfirefighter 2
·
0⤊
0⤋
4x+2=x+15+2x
3x+2=15+2x
3x=13+2x
x=13
2007-03-31 18:04:15
·
answer #10
·
answered by Ktik 2
·
0⤊
0⤋